Peru-Spain relations through opportunities in educational cooperation: Towards a new Cooperation Framework Agreement? - Delgado Rubio, Erika Carina (2023)
This thesis is centered on intensifying bilateral relations through educational cooperation between Peru and Spain. The first chapter traces the historical evolution of the relations between the two countries, spanning three centuries, with a particular focus on the evolution of education-related activities. Moreover, it delves into fundamental concepts, drawing upon literacy related to bilateralism, educational cooperation, soft power and the internationalization of higher education. The second chapter meticulously examines the interests and national priorities of both Peru and Spain concerning educational cooperation strategies. It sheds light on relevant agreements and mechanisms that elucidate the current objectives of these nations. In the concluding third chapter, the document amalgamates the significance of Peru and Spain's shared trajectory, proposing a new model of cooperation framework agreement in order to improve their relations. This model is designed to harmonize with the dynamics of the contemporary international system, adeptly addressing the challenges and opportunities that both countries currently face.